2004
DOI: 10.1103/physrevlett.92.230401
|View full text |Cite
|
Sign up to set email alerts
|

Bright Bose-Einstein Gap Solitons of Atoms with Repulsive Interaction

Abstract: We report on the first experimental observation of bright matter wave solitons for 87Rb atoms with repulsive atom-atom interaction. This counterintuitive situation arises inside a weak periodic potential, where anomalous dispersion can be realized at the Brillouin zone boundary. If the coherent atomic wave packet is prepared at the corresponding band edge, a bright soliton is formed inside the gap. The strength of our system is the precise control of preparation and real time manipulation, allowing the systema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
537
1
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(557 citation statements)
references
References 20 publications
10
537
1
9
Order By: Relevance
“…In the present case, the effect of the coupling is more complex. Given µ belongs to a bandgap in the present model if µ falls into one of the gaps in both equations (4) and (5). Further consideration demonstrates that, depending on the values of κ and OL strength ε, each gap originating from the ME spectrum either shrinks (or, sometimes, completely closes up), similar to the situation in the above-mentioned model of linearly coupled Bragg gratings, or splits into pairs of subgaps.…”
Section: Linear Spectrummentioning
confidence: 91%
“…In the present case, the effect of the coupling is more complex. Given µ belongs to a bandgap in the present model if µ falls into one of the gaps in both equations (4) and (5). Further consideration demonstrates that, depending on the values of κ and OL strength ε, each gap originating from the ME spectrum either shrinks (or, sometimes, completely closes up), similar to the situation in the above-mentioned model of linearly coupled Bragg gratings, or splits into pairs of subgaps.…”
Section: Linear Spectrummentioning
confidence: 91%
“…In this case, it is possible (as, e.g., in the experiment of Ref. [44]) to tune ω z so that it provides only a very weak trapping along the z-direction; this way, the shift in the potential trapping energies over the wells where the BEC is confined can be made practically negligible. In such a case, the potential in Eq.…”
mentioning
confidence: 99%
“…Importantly, they have also been observed in many elegant experiments using various relevant techniques. These include, among others, phase engineering of the condensates in order to create vortices [28,29] or dark matterwave solitons in them [30][31][32][33][34], the stirring (or rotation) of the condensates providing angular momentum creating vortices [35,36] and vortex-lattices [37][38][39], the change of scattering length (from repulsive to attractive via Feshbach resonances) to produce bright matter-wave solitons and soliton trains [40][41][42][43] in attractive condensates, or set into motion a repulsive BEC trapped in a periodic optical potential referred to as optical lattice to create gap matter-wave solitons [44]. As far as vortices and vortex lattices are concerned, it should be noted that their description and connection to phenomena as rich and profound as superconductivity and superfluidity, were one of the themes of the Nobel prize in Physics in 2003.…”
mentioning
confidence: 99%
“…Many intriguing phenomena that are hardly observed in conventional solid-state systems have already been reported: Bloch oscillations, Landau-Zener tunneling, [1][2][3] resonantly enhanced tunneling, 4 and solitons at the edge of the Brillouin zone. 5 A series of experiments have further demonstrated that a Bose-Einstein condensate (BEC) in a periodic potential has a critical momentum where the superfluidity becomes unstable by measuring the center-of-mass oscillations of a BEC or the decay of superfluid flows in a moving lattice. [6][7][8][9][10][11][12] As has been indicated theoretically, [13][14][15][16][17][18][19][20] this phenomenon is identified as the dynamical instability that occurs in the presence of lattice potential, and also without any energy dissipation in contrast to the well-known Landau instability of a superfluid.…”
Section: Introductionmentioning
confidence: 99%